2006
DOI: 10.1073/pnas.0508565103
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the hematopoietic transcription factor Ikaros in hypothalamic–pituitary-mediated somatic growth

Abstract: Ikaros transcription factors play critical functions in the control of lymphohematopoiesis and immune regulation. Family members contain multiple zinc fingers that mediate DNA binding and homooligomerization or heterooligomerization. Ikaros is abundantly expressed in pituitary mammosomatotrophs, where it deacetylates histone 3 sites on the proximal growth hormone (GH) promoter to silence gene expression. Ikaros-null mice display stunted growth with reduced circulating levels of the GH target factor insulin-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…GH positivity persists in the intermediate lobe of the lateral wings likely attributable to the lack of melanocorticotrope expansion that normally replaces intermediate lobe somatotrophs during development. Other cell types were not measurably affected; the number and area of immunoreactive thyrotrophs and gonadotrophs were not disproportionately different from those of wild-type littermates (Ezzat et al 2006a).…”
Section: Hypothalamic Ikaros Actions Ikaros Directs Somatotroph Expanmentioning
confidence: 86%
See 1 more Smart Citation
“…GH positivity persists in the intermediate lobe of the lateral wings likely attributable to the lack of melanocorticotrope expansion that normally replaces intermediate lobe somatotrophs during development. Other cell types were not measurably affected; the number and area of immunoreactive thyrotrophs and gonadotrophs were not disproportionately different from those of wild-type littermates (Ezzat et al 2006a).…”
Section: Hypothalamic Ikaros Actions Ikaros Directs Somatotroph Expanmentioning
confidence: 86%
“…Again, to exclude the possibility of a secondary response to immunodeficiency, we performed bone marrow reconstitution studies and showed that hematopoietic replacement does not alter IGF-I levels and restore normal growth. We carried out administration of exogenous GH with a response of circulating IGF-I levels and body weight reflecting somatic growth (Ezzat et al 2006a).…”
Section: Hypothalamic Ikaros Actions Ikaros Directs Somatotroph Expanmentioning
confidence: 99%
“…IKAROS is expressed in neuro-epithelial progenitors of the developing striatum, cortical and retinal progenitors, and the developing pituitary (Georgopoulos et al 1992;Ezzat et al 2006;Agoston et al 2007;MartinIbanez et al 2010;Alsio et al 2013). In addition to neuroepithelial cells, HELIOS is also expressed in epidermal keratinocytes (Kelley et al 1998).…”
Section: Expression and Immune Cell Phenotypesmentioning
confidence: 99%
“…The GHRH lineage is completely dependent upon ASCL1 activity because Ascl1-null embryos have very low expression of genomic screen homeobox 1 (GSH1), a homeobox domain transcription factor necessary for expression of Ghrh (28). A zinc finger containing the transcription factor Ikaros has been found to be necessary for Ghrh expression (12). Interestingly, both GSH1 and Ikaros are similarly expressed in pituitary somatotropes, and loss of either protein results in extreme dwarfism and loss of somatotropes.…”
Section: The Arcuate Nucleus and Achaete-scute Complexmentioning
confidence: 99%